Metabolic syndrome in hypertensive patients: An unholy alliance - Mulè, Giuseppe (Baishideng Publishing Group Inc, 2014)
For many years, it has been recognized that hypertension tends to cluster with various anthropometric and metabolic abnormalities including abdominal obesity, elevated triglycerides, reduced high-density lipoprotein cholesterol, glucose intolerance, insulin resistance and hyperuricemia. This constellation of various conditions has been transformed from a pathophysiological concept to a clinical entity, which has been defined metabolic syndrome (MetS). The consequences of the MetS have been difficult to assess without commonly accepted criteria to diagnose it. For this reason, on 2009 the International Diabetes Federation, the American Heart Association and other scientific organizations proposed a unified MetS definition. The incidence of the MetS has been increasing worldwide in parallel with an increase in overweight and obesity. The epidemic proportion reached by the MetS represents a major public health challenge, because several lines of evidence showed that the MetS, even without type 2 diabetes, confers an increased risk of cardiovascular morbidity and mortality in different populations including also hypertensive patients. It is likely that the enhanced cardiovascular risk associated with MetS in patients with high blood pressure may be largely mediated through an increased prevalence of preclinical cardiovascular and renal changes, such as left ventricular hypertrophy, early carotid atherosclerosis, impaired aortic elasticity, hypertensive retinopathy and microalbuminuria. Indeed, many reports support this notion, showing that hypertensive patients with MetS exhibit, more often than those without it, these early signs of end organ damage, most of which are recognized as significant independent predictors of adverse cardiovascular outcomes.